Inheritance of the Flesh Color and Shape of the Tuberous Root of Sweet Potato (Ipomoea batatas [L.] Lam.) - Alfredo Morales; Iván Javier Pastrana Vargas; Dania Rodríguez del-Sol; Orelvis Portal; Yoel Beovides García; Yuniel Rodríguez García; Alay Jiménez Medina; Yusbiel León Valdivies; Vaniert Ventura Chávez (Horticulturae)
The continued success of any conventional sweet potato breeding program is limited by knowledge of the inheritance of the traits under study, such as flesh color and tuberous root shape, because of the difficulty of segregating color frequencies by visual separation. The objective of this study was to understand the mode of inheritance of these genetic traits. The cross blocks were established at the Research Institute of Tropical Roots and Tuber Crops (INIVIT-Cuba). Eight parental genotypes of known compatibility were selected, with contrasting phenotypic characteristics to develop segregating populations. To express color objectively, the CIE L*a*b* color space was used (L*: lightness; a* and b*: chromatic coordinates), and four morphometric variables related to the shape and dimensions of the tuberous root were evaluated. From 2419 reciprocal crosses, 2045 botanical seeds and 1764 seedlings were obtained. Incomplete dominance of the white and purple flesh colors over the orange color was observed, as well as transgressive segregation for purple, orange, and white flesh colors and for the shape of the tuberous root. The results allowed us to propose a genetic model of biparental crosses for the improvement of the flesh color of sweet potato (Ipomoea batatas [L.] Lam.), as well as a predictive formula of the progeny to be selected.